A Contextual Analysis of Ritual Fauna and Socially Integrative Architecture in the Tonto Basin, Arizona. Issue 3 (3rd July 2018) - Schwartz, Christopher W.
Abstract : The frequent deposition of animals in public spaces suggests a key role in public rituals in the prehispanic U.S. Southwest. Using ethnographic evidence and large-scale analysis of faunal remains in the Tonto Basin area of central Arizona, I ask whether ritual fauna cluster in socially integrative spaces and what implications this had for integrating migrant Puebloan populations with local people. The Tonto Basin area is typically considered Hohokam, but exhibits influence from neighboring Sinagua and Puebloan regions. The emergence of the Salado phenomenon and public architecture in the region is evidence of broad sociopolitical and religious change involving specific treatments and storage of fauna. I find that ritual fauna cluster in room contexts associated with socially integrative architecture suggest a centralization of ritual practice and storage. Ultimately, Tonto Basin communities targeted specific taxa for the enactment of public activities, aiding in the integration of non-local people.